Female genital cutting : cultural conflict in the global community - Boyle, Elizabeth Heger, 1962- (Johns Hopkins University Press, 2002)
"In this study, sociologist Elizabeth Heger Boyle examines this controversial issue from the perspectives of the international system, governments, and individuals. Drawing on previous scholarship, records of international organizations, demographic surveys, and the popular media, Boyle examines how the issue is perceived and acted upon at international, national, and individual levels. Grounding her work in the sociological theory of neoinstitutionalism, Boyle describes how the choices made by governments and individual women are influenced by the often conflicting principles of individual human rights and sovereign autonomy. She concludes that, while globalization may exacerbate such conflicts, it can ultimately lead to social change."--Jacket